Incidence of Malignancies and the Association with Biological Disease-Modifying Antirheumatic Drugs in Japanese Patients with Rheumatoid Arthritis: A Time-Dependent Analysis from the IORRA Patient Registry - Masayoshi Harigai; Eiichi Tanaka; Eisuke Inoue; Ryoko Sakai; Naohiro Sugitani; Shigeyuki Toyoizumi; Naonobu Sugiyama; Hisashi Yamanaka (Rheumatology and Therapy)
Abstract Introduction Patients with rheumatoid arthritis (RA) may have an increased malignancy risk versus the general population, potentially elevated by biological disease-modifying antirheumatic drug (bDMARD) use. Using patient registry data, we determined malignancy risk, stratified by bDMARD use, among Japanese patients with RA versus the Japanese general population and investigated whether bDMARD use is a time-dependent risk factor for the development of malignancy. Methods Patients aged ≥ 18 years with ≥ 2 data entries of RA in the IORRA (Institute of Rheumatology, Rheumatoid Arthritis) patient registry, enrolled from January 2013–December 2018, were identified (‘All RA’ cohort). Patients were stratified into bDMARD (≥ 1 bDMARD received) or non-bDMARD (no history of bDMARDs) sub-cohorts. Malignancy incidence rates and standardized incidence ratios (SIRs) with 95% confidence intervals (CIs) versus the Japanese general population were calculated. Risk of RA medication use was analyzed using a time-dependent Cox proportional hazards model, after adjusting for covariates. Results A total of 8020 patients were identified for the All RA cohort; 2187 and 5833 for the bDMARD and non-bDMARD sub-cohorts, respectively. For all three cohorts, incidence of overall malignancies was similar versus the Japanese general population. Incidence of specific malignancies was also similar, but incidence of lymphoma was higher for all three cohorts (SIRs [95% CIs] 3.72 [2.71–4.93], 5.97 [3.34–9.59], and 2.79 [1.82–4.02], respectively). In the bDMARD sub-cohort, no increase in SIRs was observed for other site-specific malignancies. In the All RA cohort, use of methotrexate, tacrolimus, glucocorticoids, non-steroidal anti-inflammatory drugs, and bDMARDs were not associated with the risk of overall malignancy; the hazard ratio (95% CI) was 1.36 (0.96–1.93) for bDMARD use. Increased disease activity was a time-dependent risk factor of overall malignancy with a hazard ratio (95% CI) of 1.35 (1.15–1.59). Conclusions The use of bDMARDs was not a time-dependent risk factor for malignancy.